ANALISIS KUNJUNGAN KERJA DPRD RIAU KE AMERIKA SERIKAT DALAM PENINGKATAN SUMBER DAYA MANUSIA - Maharani, Ceysha Citra; Pakpahan, Saman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The working visit of the Riau Provincial House of Representatives (DPRD) to the United States is part of parliamentary diplomacy aimed at improving the capacity of council members in the field of human resource development (HR). Through this activity, the Riau DPRD seeks to gain experience and learn from the practices of education governance and economic development policies in developed countries. The visit is a strategy to expand international cooperation networks and support regional competitiveness in the era of globalization. This study uses a qualitative approach with data collection techniques through interviews and documentation of archives, news, and official reports. The analysis uses liberalism theory, state level analysis, and parliamentary diplomacy theory to explain the role of the DPRD as a regional diplomacy actor. This approach allows researchers to understand the dynamics of DPRD working visits in the context of international relations and regional development in depth. The results show that the Riau DPRD working visits have strategic value as a means of knowledge transfer and policy exchange between institutions. However, the implementation of these activities has not been fully effective due to weak evaluation mechanisms and follow-up on the results of the visits. A better reporting and transparency system is needed so that overseas visits can produce real policies in improving the quality of human resources in Riau Province. Keywords: Riau DPRD, parliamentary diplomacy, working visits, human resources, regional development.